Professores de street dance do estado de São Paulo: formação, saberes e ensino - Valderramas, Caroline Guimarães Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Dancing expresses human and cultural heritage aspects of a given society and are mostly taught by licensed teachers or respected and seasoned practitioner . The main goal of this present research is analyze how those individuals who dedicate themselves to teach Street Dance in the São Paulo State got their formal training to do so ; and also theirs ideas and considerations about the challenges and limitations of their academic training to become teachers of such subject. This work is structured as follows: first the author brings us concepts about Culture, Hip Hop Culture, its origins and how the subject Street Dance is perceived and understood. On a second moment the author reviews what kind of studies and training are mandatory for someone to become a professional dancer or a Physical Education teacher; how PE teachers approach the teachings of dance techniques and how they accomplished their know how to do so, through academic/ professional training or just experiencing and practicing without formal, conventional education. Ten Street Dance Teachers of São Paulo State were interviewed and through their input the following conclusions became clear: A) None of them have ever received formal academic training in dancing; few of them hold degrees in Physical Education and most of them work as teachers licensed or authorized by organizations such as CREF or DRT. B) They believe there is no such thing as a unique or definitive line of education to become a professional in this field. C) They could not reach a consensus about the term Street Dance . D) They do not believe that there is a specific method to teach this dancing style. They rather believe that each teacher brings his or her own experiences to the class, which explains why each set of Street Dance students show different features and characteristics. E) They agree that getting a formal academic education... Complete abstract click electronic access below)
Keywords: Dança; Professores de dança; São Paulo (Estado); Dança de rua; Street dance; Dance teachers